2017
DOI: 10.1071/rd16513
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin potentially acts directly on swine ovary by modulating granulosa cell function and angiogenesis

Abstract: Melatonin exerts well-known reproductive effects, mainly acting on hypothalamic gonadotrophin-releasing hormone release. More recent data suggest that melatonin acts directly at the ovarian level, even if, at present, these aspects have been only partly investigated. Swine follicular fluid contains melatonin and its concentration is significantly reduced during follicular growth. Therefore, the present study was undertaken to examine the effects of melatonin, used at physiological concentrations, on cultured s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…There was no difference in FF concentrations of estradiol and progesterone between the placebo and melatonin groups, suggesting that melatonin is not significantly associated with the synthesis of these hormones in the follicle. This is in contrast to previous findings in swine models ( 24 ).…”
Section: Discussioncontrasting
confidence: 99%
“…There was no difference in FF concentrations of estradiol and progesterone between the placebo and melatonin groups, suggesting that melatonin is not significantly associated with the synthesis of these hormones in the follicle. This is in contrast to previous findings in swine models ( 24 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Papers performed in various mammalian species reported that melatonin protects the adult ovary from the harmful effects of a variety of treatments and compounds, including nicotine [ 30 , 32 – 34 , 36 , 42 ]. Melatonin is able to scavenge the most toxic free radical as a robust antioxidant [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…α7 receptors are also involved in angiogenic and neurogenic activity, and have anti-apoptotic effects. As pineal MT upregulates the α7nAChR over the circadian rhythm [ 26 ], the role of the α7nAChR in modulation of the various facets of embryogenesis will be important to determine.…”
Section: Melatonin Synthesis and Signaling Ways Of Embryogenesismentioning
confidence: 99%